臺灣、美國與新加坡國中階段幾何教材內容之分析比較 Geometry Content of Middle School Textbooks in Taiwan, the United States, and Singapore - 楊德清 Der-Ching Yang (National Taiwan Normal University, 2015)
本研究採內容分析法以比較臺灣「康軒數學」、美國「連結數學」與新加坡「新課程數學」在國中階段幾何教材總題數、佈題方式與表徵型態，以及幾何內容特色之差異。結果顯示：三套教科書在幾何教材總題數具顯著差異性，美國「連結數學」之幾何總題數顯著多於臺灣「康軒數學」與新加坡「新課程數學」。三套教科書在佈題方式亦有差異；美國「連結數學」有將近三分之一的問題屬開放型問題，但是「康軒數學」與「新課程數學」兩套教材之幾何題目安排高達九成五以上皆為封閉型問題。三套教材在表徵型態方面，以「聯合型態問題」與「文字型態問題」部分所占比例最高，約有七至八成以上。研究亦發現，三套教材在幾何主題內容有部分差異，且三套教材亦各有其特色。最後，期望本研究之發現，可提供未來數學教科書設計之參考。 This study applied the content analysis method to compare the differences in the geometry problems, problem-posing methods, representational types, and characteristics of geometry content of middle school mathematics textbooks among Kang Hsuan (KH) in Taiwan, Connected Mathematics Program (CMP) in the United States, and New Syllabus Mathematics (NSM) in Singapore. The results reveal significant differences in the total geometry problems and problem-posing methods among the three textbooks. The CMP included approximately one-third open-ended problems; however, the KH and NSM textbooks included more than 95% closed-ended problems. Regarding representation types, all three textbooks presented combined problems and verbal problems. In addition, the results show that the three textbooks have different characteristics. The findings of this study can serve as a reference for designing mathematics textbooks in the future.